From 78% oxygen saturation to 95% in 60 minutes: Osler-Weber-Rendu syndrome endovascular treatment - Szmygin, Maciej; Sojka, Michał; Pyra, Krzysztof; Jargiełło, Tomasz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2020)
Pulmonary arteriovenous malformations (PAVMs) are abnormal communications between the pulmonary artery and pulmonary vein without an intervening capillary system. PAVMs are most commonly associated with Hereditary Hemorrhagic Telangiectasia (HHT) also known as Osler-Weber-Rendu syndrome, a rare autosomal dominant disorder [1]. Acquired PAVMs occur in patients with chronic liver disease, history of cardiosurgical procedures or thoracic trauma, metastatic thyroid cancer or Fanconi syndrome [2]. The presenting symptoms including dyspnea, hypoxemia and chest pain result from right-to-left shunt, cardiac volume overload and destruction of lung parenchyma. Establishing the final diagnosis is difficult and requires multi-disciplinary workup. Traditional surgical management of PAVM has been gradually replaced by minimally invasive embolotherapy which became a gold standard of treatment [3].